Nitrogen Fertilization of Soybean in Mississippi Increases Seed Yield but Not Profitability. (1st July 2018) - McCoy, Justin M.; Kaur, Gurpreet; Golden, Bobby R.; Orlowski, John M.; Cook, Donald; Bond, Jason A.; Cox, Michael S.
Abstract : Core Ideas: Nitrogen applications increased soybean yields by 4% for sandy/silt loam soil. Nitrogen applications increased soybean yields by 8% for clay soil. Yield components response to N applications parallels the trends observed for yield. Nitrogen application is not an economically feasible way to improve soybean yield. Trials were conducted in 2014 and 2015 at Delta Research and Extension Center in Stoneville, MS, to evaluate soybean [ Glycine max (L.) Merr.] response to N sources (ammonium sulfate [AMS], polymer‐coated urea [PCU], urea+urease inhibitor [Urea+NBPT, N‐(n‐butyl) thiophosphoric triamide]), N application rate (0, 45, 90, 135, 179 kg N ha −1 ) and timing (V4, R1), on two soil textures (sandy/silt loam and clay) that are commonly used for soybean production in Mississippi. Urea+NBPT produced 5 and 8% greater aboveground biomass than AMS and PCU on sandy/silt loam soil. Nitrogen applications at the V4 growth stage resulted in 6% greater biomass production than the R1 application timing on sandy/silt loam. Averaged over N rates where a seed yield increase was observed, N applications increased soybean yields by 4% for sandy/silt loam soil and by 8% for clay soil compared to unfertilized soybeans. No differences were observed for soybean yields between N rates of 45, 90, 135, and 179 kg N ha −1 . Soybean yield from PCU was 2.5% greater than urea+NBPT on sandy/silt loam soil. Nitrogen rates influenced soybean yield components including pods and seeds plant −1 on sandy/silt loam soil as well as seeds and seed mass plant −1 on clay soil. Yield component response to N fertilization parallels the trends observed with overall soybean seed yield increases on both soil textures. Despite increases in seed yield observed with N application, analysis of partial returns suggests that N application is not an economically feasible way to improve soybean seed yield.